U.S. Banking Deregulation, Small Businesses, and Interstate Insurance of Personal Income - Yuliya Demyanyk; Charlotte Ostergaard; Bent E. Sørensen (Norges Bank, 2006)
We estimate the effects of deregulation of U.S. banking restrictions on the amount of interstate personal income insurance during the period 1970-2001. Interstate income insurance occurs when personal income reacts less than one-to-one to state-specific shocks to output. We find that income insurance improved after banking deregulation, and that this effect is larger in states where small businesses are more important. We further show that the impact of deregulation is stronger for proprietors' income than other components of personal income. Our explanation of this result centers on the role of banks as a prime source of small business finance and on the close intertwining of the personal and business finances of small business owners. Our analysis casts light on the real effects of bank deregulation, on the risk sharing function of banks, and on the integration of bank markets.
hdl:11250/2498365
Keywords: 330; financial deregulation; integration of bank markets; interstate risk sharing; small business finance